2006
DOI: 10.1111/j.1365-2141.2006.06037.x
|View full text |Cite
|
Sign up to set email alerts
|

William Hewson (1739–74): the father of haematology

Abstract: SummaryWilliam Hewson has been called the father of haematology. Initially working alongside the Hunter brothers in London in the mid-18th century, he advanced our knowledge of red and white cells (but mistakenly thought some red cells started as white cells and could not recognise different varieties of white corpuscles), showed that it was fibrinogen and not the cells that led to coagulation, greatly advanced our knowledge of the lymphatic system in humans, fishes and amphibians, explored the functions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 8 publications
0
39
0
2
Order By: Relevance
“…Indeed, he noted that the gland was disseminated with "particles" similar to those found in peripheral blood and in the lymph and thought that the thymus worked in the early months of life when the organism most needed these "particles" [16]. What then becomes of these particles after they are mixed with the circulation blood?… They are, we believe, carried with the blood to the spleen… and the spleen has the power of separating them from other parts of the blood" [17]. We have proved that vast numbers of central particles made by the thymus and the lymphatic glands are poured into the blood vessels through the thoracic duct and if we examine the blood attentively we see them floating in it.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Indeed, he noted that the gland was disseminated with "particles" similar to those found in peripheral blood and in the lymph and thought that the thymus worked in the early months of life when the organism most needed these "particles" [16]. What then becomes of these particles after they are mixed with the circulation blood?… They are, we believe, carried with the blood to the spleen… and the spleen has the power of separating them from other parts of the blood" [17]. We have proved that vast numbers of central particles made by the thymus and the lymphatic glands are poured into the blood vessels through the thoracic duct and if we examine the blood attentively we see them floating in it.…”
mentioning
confidence: 90%
“…Finally, he confirmed that the thymus becomes smaller with aging and assumed that some other tissue could take on its functions during mature age but he also found that the size of the organ can be rapidly reduced in the course of acute and chronic diseases [17].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Relaxation of the body wall muscles can lower intracoelomic pressure to values close to that of the surrounding sea water. The term clot is commonly used to denote the formation of a haemostatic soft mass in a fluid such as blood or haemolyph and has been used a synonym for the congealing of cell-free fluid since William Hewson showed, in the 18th century, that blood coagulation is attributable to the clotting of plasma rather than changes in the cellular constituents (Doyle 2006). However, clotting in sipunculans does not involve the congealing of cell-free coelomic fluid (Blanco 2007;Blanco et al 2008;Dybas 1976;Towle 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the assessment of chronic stress (Möstl et al, 2002;Negrão et al, 2004;Ferranti et al, 2011) is performed by measuring glucocorticoid hormones (cortisol or corticosterone) in blood, saliva, urine and feces. Moreover, hematological parameters have been reported to provide valuable information on the immune and physiological status of the animal, distinguishing health and stress status (Doyle, 2006).…”
Section: Introductionmentioning
confidence: 99%